P540 Longitudinal Dynamics of Gut Microbiome and Metabolome After Biological Therapy in Inflammatory Bowel Diseases. (21st January 2022) - Ahmed, M; Metwaly, A; Hammoudi, N; Meng, C; Köhler, N; Le Bourhis, L; Pauling, J; Kleigrewe, K; Allez, M; Haller, D
Abstract: Background: Inflammatory bowel diseases (IBD), including Crohn's disease (CD) and ulcerative colitis (UC) are chronic inflammatory conditions that affect the gastrointestinal tract. Biological therapy with monoclonal antibodies has provided significant benefit for patients with IBD, resulting in clinical and endoscopic remission. Gut microbiome alterations were shown to serve as a marker of response to treatment in IBD. The aim of the study is to characterize gut microbiome and metabolome in patients with CD and UC after initiation of biological therapy. Methods: We studied a prospective cohort of 41 CD and 39 UC patients initiating biological therapy. Biological therapy included anti-TNF (Adalimumab, Infliximab and Golimumab), anti-α4β7 integrin (Vedolizumab) or anti-IL-12/23 p40 antibody (Ustekinumab). One-year follow up showed that up to 60% of the patients achieved clinical and endoscopic remission. Fecal samples and mucosal biopsies were collected both at baseline and 14 or 52 weeks after initiation of therapy. Microbiota and metabolite changes were analyzed using 16S rRNA gene sequencing and targeted/untargeted metabolomics. Results: Longitudinal profiling of luminal and mucosal bacteria reflected the individual patient-related variations over the study duration. CD and UC patients showed distinct luminal and mucosal bacterial communities. Bacterial dysbiosis was significantly higher in patients with CD than with UC, as shown by community richness and diversity. While fecal microbiota of patients with CD was enriched in Escherichia coli and Bacteroides, both Faecalibacterium and Bifidobacterium were enriched in UC. In contrast to fecal bacterial communities, mucosal bacteria from patients with ileal and colonic CD showed a clear separation of microbial profiles based on disease location. Members belonging to Haemophiles, Fusobacterium, and Escherichia coli were significantly more abundant in IBD patients with active disease. Machine-learning based analysis showed that fecal and biopsy profiles equally classified patients based on their disease subtype, with an area under the curve (AUC)=0.86. Metabolite profiling revealed enrichment of platelet-activating factor and the glycosphingolipid lactosylceramide in inflamed phenotypes. Conversely, enrichment of bile acids, such as deoxy cholic acid, chenodeoxycholic acid and Lithocholic acid was observed in responders or patients during remission. Conclusion: Gut microbial and metabolomic profiling revealed associations between gut microbial taxonomic or functional profiles and IBD subtypes. The association between enrichment of fatty acids and bile acids and disease activity suggests an important role of these pathways in the development or the resolution of intestinal inflammation.